Prenatal PCB Exposure and Thymus Size at Birth in Neonates in Eastern Slovakia - Park, Hye-Youn (National Institute of Environmental Health Sciences, 2008)
BACKGROUND: Polychlorinated biphenyls (PCBs) are ubiquitous environmental toxicants, for which animal studies demonstrate immunotoxic effects, including thymic atrophy and suppressed immune responses; human investigations of similar end points are sparse. The thymus is essential for the differentiation and maturation of T-cell lymphocytes. OBJECTIVES: The objective of this study was to examine the association between prenatal PCB exposures and estimated thymus volume in infants from eastern Slovakia, a region where PCBs were produced until 1984. METHODS: Mothers were enrolled at delivery, and maternal blood samples were collected for analysis of 15 PCB congeners, p,p′-DDT [1,1,1-trichloro-2,2′-bis(p-chlorophenyl)ethane], and p,p′-DDE [1,1-dichloro-2,2-bis(p-chlorophenyl)ethylene]. Each mother was interviewed to obtain information on sociodemographic characteristics, past pregnancies, occupational history, medication history, and living environment. Neonatal thymus volume was estimated using ultrasound measurements on the third or fourth day after birth. Thymic index was calculated on 982 newborns from mothers with PCB measurements. We developed a predictive model of the natural log of the thymic index using multiple linear regression with covariates selected from the bivariate analyses. RESULTS: Prenatal PCB exposure was associated with a smaller thymic index at birth [β= −36 (natural log-transformed; nanograms per gram lipids); p = 0.047]. District of residence and delivery also predicted thymic index. Male sex, later gestational age, larger birth weight z-score, and Roma ethnicity were associated with a larger thymic index, whereas respiratory illness was associated with a lower thymic index. CONCLUSIONS: This study provides the first evidence to date that PCB exposure in neonates is associated with a smaller thymic volume, suggesting possible impaired immunologic development.